Understanding the gap between the gender equality and social inclusion policy and implementation in the energy sector: the case of Nepal - Buchy, Marlene; Shakya, Shristi (Elsevier, 2023)
Social norms are often put forward to explain resistance to gender equality and social inclusion (GESI), and women continue to be largely absent from decision-making positions in the energy sector worldwide. However, there is limited research on the institutional mechanisms of policy-making and implementation at different scales within a federal system. Using Nepal as a case study, this paper explores why, despite commitments, progress toward GESI objectives in the energy sector has been slow. Based on a review of energy policies, and interviews at federal, provincial and local government spheres, this paper focuses on the institutional and policy processes at play within the energy sector and between the three spheres of the federal system (the national, provincial and local). It examines the extent to which these processes undermine the implementation of inclusion policy. Understanding the broader institutional processes helps to identify different types of bottlenecks compromising progress in GESI: those which are linked to deficient policy regimes which cannot be addressed solely through additional GESI-focused interventions, and those which can be characterized as resistant to GESI-related issues. The aim of this research is also to understand why Nepal’s public energy institutions, despite a constitutional commitment to gender equality and non-discrimination based on caste, class, ethnicity and religion, seem so reluctant to mainstream GESI within its policies and practice. The paper concludes that GESI implementation in the energy sector suffers from limited human resources, a narrow conceptual framing and delays in policy development and implementation within different spheres of the federal system. Moreover, shortcomings related to GESI policy-making and implementation should be considered within the broader context of federalism. Therefore, to support GESI policy implementation, bureaucratic as well as local-level ownership of the concept and its relevance for sustainable development must be developed and strengthened.